Measuring The Relationship Between The Dimensions of Health Marketing (NTU journal for Administrative and Human Sciences (JAHS), 2023)
The current research aims to diagnose health marketing with the expressed dimensions of (service, price, promotion, distribution, physical evidence, individuals, operations) at Al-Zahrawi Private Hospital in Nineveh Governorate, and the questionnaire was adopted as a main tool for data collection, and the statistical program (spss) was relied on. For the purpose of analyzing the data collected from a sample of (200) respondents from the clients of the field in question, a set of conclusions was reached that confirm the availability of those dimensions and at high levels in the organization in question. Adopted by the management of the organization in question in order to achieve its objectives.